2006
DOI: 10.1007/s00125-006-0457-3
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training increases insulin-stimulated glucose disposal and GLUT4 (SLC2A4) protein content in patients with type 2 diabetes

Abstract: Aims/hypothesis Exercise enhances insulin-stimulated glucose transport in skeletal muscle through changes in signal transduction and gene expression. The aim of this study was to assess the impact of acute and short-term exercise training on whole-body insulin-mediated glucose disposal and signal transduction along the canonical insulin signalling cascade. Methods A euglycaemic-hyperinsulinaemic clamp, with vastus lateralis skeletal muscle biopsies, was performed at baseline and 16 h after an acute bout of exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
122
2
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(144 citation statements)
references
References 53 publications
(86 reference statements)
12
122
2
8
Order By: Relevance
“…We and others (21,22) have shown that aerobic exercise has a dose-and intensity-related effect to increase insulin signaling and glucose transporter content in skeletal muscle. Exercise training increases insulin-stimulated glucose disposal and GLUT-4 (SLC2A4) protein content in obese patients with type 2 diabetes (22). High levels of sedentary time produce the reverse effect.…”
Section: Discussionmentioning
confidence: 82%
“…We and others (21,22) have shown that aerobic exercise has a dose-and intensity-related effect to increase insulin signaling and glucose transporter content in skeletal muscle. Exercise training increases insulin-stimulated glucose disposal and GLUT-4 (SLC2A4) protein content in obese patients with type 2 diabetes (22). High levels of sedentary time produce the reverse effect.…”
Section: Discussionmentioning
confidence: 82%
“…The landmark diabetes prevention studies have proven the efficacy of exercise intervention in preventing progression from IGT to diabetes [9,11,12]. We have recently shown that just 7 days of exercise training led to increased glucose disposal and muscle GLUT4 protein content in middle-aged, obese subjects with type 2 diabetes (mean age 45 years, BMI 36 kg/m 2 ) [15]. Since early-onset type 2 diabetes is characterised by obesity and severe insulin resistance, we chose to investigate the effect of exercise intervention in younger subjects with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller studies have shown that exercise improves insulin sensitivity and glucose metabolism [13,14]. We have recently shown that short-term exercise training increased insulin sensitivity by more than 50% in obese middle-aged patients (mean age 45 years) with type 2 diabetes [15]. In these patients the main biochemical change was an increase in glucose transporter 4 (GLUT4) protein content in skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Training can enhance the responsiveness of skeletal muscles to insulin with increased expression and/or activity of proteins involved in glucose metabolism and insulin signaling. Moderate training may increase glycogen synthase activity and GLUT4 protein expression but not insulin signaling [29]. Fat oxidation is also a key aspect of improved insulin action, and training increases lipid storage in muscles and fat oxidation capacity [30].…”
Section: Discussionmentioning
confidence: 99%